2017
DOI: 10.1177/1363460717737488
|View full text |Cite
|
Sign up to set email alerts
|

The use of gender in the interpretation of BDSM

Abstract: In this article, we explore the ways BDSM practitioners negotiate gender. Based on 32 in-depth interviews with BDSM practitioners and thousands of message board posts from the then-largest online BDSM community in the USA, we explore the explanatory frameworks BDSM practitioners use to (1) downplay and (2) emphasize dominant notions of gender to make sense of BDSM practices and experiences. In so doing, we discuss some ways BDSM practices and interpretations may both challenge and reproduce broader societal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…As a tenured university professor, as someone who teaches classes and publishes articles on sexuality, as the resident ''sex expert''-I had come to a point in life where I was uniquely empowered to be vulnerable. Thus, while some research (Weiss, 2011) has suggested that playing as a male bottom can be construed as emasculating or humiliating, consistent with other research (Simula and Sumerau, 2019), I ultimately experienced quite the opposite: My vulnerability was empowering and, at least in one sense, a kind of demonstration to myself that I now had sufficient power in my life that I could afford to give some away (see Savran, 1996Savran, , 1998.…”
Section: Reflecting On Gender Power and Riskmentioning
confidence: 69%
“…As a tenured university professor, as someone who teaches classes and publishes articles on sexuality, as the resident ''sex expert''-I had come to a point in life where I was uniquely empowered to be vulnerable. Thus, while some research (Weiss, 2011) has suggested that playing as a male bottom can be construed as emasculating or humiliating, consistent with other research (Simula and Sumerau, 2019), I ultimately experienced quite the opposite: My vulnerability was empowering and, at least in one sense, a kind of demonstration to myself that I now had sufficient power in my life that I could afford to give some away (see Savran, 1996Savran, , 1998.…”
Section: Reflecting On Gender Power and Riskmentioning
confidence: 69%
“…Bauer, in an interview study of lesbian/dyke/queer/trans people practicing BDSM (Bauer, 2014), noted several connections between BDSM and sexual interactions that concur with the findings of Simula and Sumerau (2017). BDSM sexual subculture provided its members with a "high degree of reflection about sexuality and relationships and led them to distinguish between the emotional, sexual, and BDSM level as criteria for non/exclusivity in relationships" (Bauer, 2010: 146).…”
Section: Interaction Between Sex and Kinkmentioning
confidence: 88%
“…Ninety-five percent of their sample of 178 men and 47 women indicated that SM activities were as satisfying, or more satisfying, than sex without SM, and 30% reported that "S/M activity was essential to a gratifying sexual experience" (Moser and Levitt, 1987: 331). Finally, Simula and Sumerau (2017) reported that a majority of participants in their qualitative study of 32 BDSM practitioners in the United States strongly distinguished sexual behavior in the context of BDSM scenes from "vanilla" sex (i.e. sex that does not involve kink) and that while BDSM is "often 'sexual', it is nonetheless distinctly not 'sex'" (216).…”
Section: Interaction Between Sex and Kinkmentioning
confidence: 99%
“…Hegemonic masculinity is constructed in relation to femininities, and subordinate and marginalised masculinities (Connell, 1987). For example, through empirical research, it was found that in some cases, bondage, discipline (or domination), sadism and masochism (BDSM) practitioners emphasized gender to understand their BDSM activities through gendering power relations and performance styles, using hegemonic gender beliefs to reinforce their gender identity projects (Simula and Sumerau, 2017). Weeks (2005: 59) elucidates that, ‘both masculinity and femininity are “gender projects”, through which social practices over time construct and transform the relations between men and women [and amongst men]’.…”
Section: Hegemonic Masculinity and Chemsexmentioning
confidence: 99%